The influence of galvanic currents and voltage on the proliferation activity of lymphocytes and expression of cell surface molecules - Podzimek, Štěpán; Hána, Karel; Mikšovský, Martin; Poušek, Lubomír; Matucha, Petr; Meloun, Milan; Procházková, Jarmila (Folia biologica (Praha), 2008)
Release of metal ions from dental metal fillings supported by galvanism can cause local or general pathological problems in sensitive and genetically susceptible individuals. We aimed to investigate in vitro lymphocyte responses and expression of surface molecules influenced by galvanic currents and voltage. Human peripheral blood lymphocytes were influenced by galvanic currents and voltages and lymphocyte proliferation was measured. Control samples were not exposed to the influence of galvanism. We also studied the expression of surface molecules by the FACS analysis. A 15-h and shorter influence of almost all tested currents and voltages caused a significant decrease in lymphocyte proliferation and the 15-h influence of 20 microA currents significantly increased expression of surface molecules CD 19, 11a/18, 19/69 and 19/95. An influence of 10 and 3 microA currents led to a significant decrease in the expression of surface molecules CD 3, 11a/18, 3/69 and 3/95 and to a significant increase in CD 19 expression. An 80 mV voltage influence led to a significant decrease in the expression of surface molecules CD 3, 11a/18, 3/69, 3/95, 19/69 and 19/95, and 200 and 300 mV voltages significantly decreased the expression of surface molecules CD 3, 19, 11a/18, 3/95 and 19/95 and significantly increased CD 19/69 expression. A long-lasting influence of galvanism can, in sensitive and genetically susceptible individuals, influence lymphocyte proliferation and surface molecule expression. The threshold for pathological values of 5 microA for galvanic currents and 100 mV for galvanic voltage was confirmed.
Keywords: Antigens, CD; Biomarkers; CD antigeny; proliferace buněk; Cell Membrane; biologické markery; elektřina; lidé; Electric Stimulation; Electricity; Cell Proliferation; lymfocyty; elektrická stimulace; Humans; Lymphocytes; buněčná membrána